An Evaluation Cost Model of Consideration Sets - Hauser, John R.; Wernerfelt, Birger (Journal of Consumer Research, 1990)
Abstract If utility (net of price) varies by consumption occasion, the consideration set of a rational consumer will represent trade-offs between decision costs and the incremental benefits of choosing from a larger set of brands. If evaluating a brand decreases biases and uncertainty in perceived utility, the decision to evaluate a brand for inclusion in a consideration set is different from the decision to consider an evaluated brand. The decision to consume is, in turn, different from the decision to consider. This article provides analytical expressions for these decision criteria and presents four aggregate implications of the model: (1 ) distributions of consideration set sizes, (2) order-of-entry penalties, (3) dynamic advertising response, and (4) competitive promotion intensity.